PREVALENCE OF TICK AND ANAPLASMA INFESTATIONS IN RELATION TO SEX, AGE AND LOCATION OF BUNAJI CATTLE IN KADUNA STATE, NIGERIA - Bulus, L.; Sanusi, M.; Bello, K.M.; Adamu, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study investigates the prevalence of ticks and anaplasma parasites in free-grazing Bunaji cattle of Ikara and Makarfi Local Government Areas, Kaduna State, Nigeria. Five herds of Bunaji cattle were selected from each Local Government Area, of which 200 animals were randomly selected. Blood samples from all the 200 cattle were obtained for isolation and identification of anaplasma parasites using microscopic technique. Packed Cell Volume (PCV) and Total Protein (TP) levels were also analyzed for each blood sample. Out of the 200 cattle examined, 77 (38.5%) were infested with ticks and a total of 368 ticks were collected. Four (4) genera of ticks were identified: Amblyomma spp. (37.8%), Hyalomma spp. (31.8%), Rhipicephalus spp. (13.6%), and Boophilus spp (16.8%) were the genera identified. Anaplasma parasites were identified in only 4 cattle (2%) of the total sample and (5.2%) of the tick-infested cattle. The study revealed that male cattle had a significantly (P < 0.05) higher prevalence (51.1%) than females with (34.6%). On the other hand, young cattle had a significantly (P < 0.05) higher prevalence (53.8%) compared to adults (33.1%). A significant difference (P<0.05) was observed in the mean values of packed cell volume (PCV) between those positive for anaplasma parasite and those that were negative for the parasites, whereas, there was no Significant difference (P<0.05) in the values of total protein (TP) between those positive and those negative for anaplasma parasite. In conclusion, Male Hyalomma species recorded higher (36.2%) prevalence, while female Amblyomma species was found to be dominant (43.7%). It is recommended that, prophylactic and curative measures be emphasized on male and young cattle with 51.1% and 53.8% level of infestation respectively.